Analisis Kesulitan Siswa dalam Memahami Konsep Laju Reaksi (Systematic Review) - Santa Ira Yustina Mersa; Suandi Sidauruk; Maya Erliza Anggraeni (FKIP Universitas Palangka Raya, 2024)
This study uses a systematic review method. The research was conducted to describe and summarize the results of analyses related to students' difficulties in understanding the concept of reaction rates. The sample in this study consists of three theses on difficulties in understanding the concept of reaction rates. The data in this research are the students' difficulties based on the patterns of their answers and the instruments used in each thesis. The analysis of the instruments includes Basic Competencies (KD) and Operational Verbs (KKO) from the three theses, while the students' difficulties are analyzed by comparing the patterns of their answers. The results of the study on students' difficulties in understanding the concept of reaction rates are as follows: (1) students define that the reaction rate is the increase in the concentration of one of the reactants per unit time, (2) students consider the reaction rate to be, (3) students regard the index value as the coefficient used to divide the rate expression and use the index to balance the reaction, (4) in determining the reaction order based on experimental data tables, students consider that the reaction order is the quotient of the rate value divided by the concentration of the reactant, (5) students believe that the total reaction order is obtained by multiplying the concentration exponents or reaction orders, (6) students have difficulties with the chemical calculation concept in determining the reaction order based on experimental data tables, assuming that the reaction order is the quotient of the rate value divided by the concentration of the reactant, (7) students consider that the reaction order value is the concentration value in a reaction rate equation, and (8) students are not meticulous in interpreting the known data into their calculation formulas and believe that the reaction rate value can be obtained from the coefficient of the product.